2012
DOI: 10.1590/s0037-86822012000400008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of hepatitis B virus among the indigenous population of the Curuçá and Itaquaí Rivers, Javari Valley, State of Amazonas, Brazil

Abstract: Introduction: Hepatitis B virus (HBV) infection is one of the most serious public health problems in the world. In Brazil, HBV endemicity is heterogeneous, with the highest disease prevalence in the North region. Methods: A total of 180 samples were analyzed and subjected to polymerase chain reaction (PCR) and semi-nested PCR of the HBV S-gene, with the aim of determining the prevalence of HBV-DNA (deoxyribonucleic acid) in indigenous groups inhabiting the areas near the Curuçá and Itaquaí Rivers in the Javari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…This DSEI also presented high levels of the three vulnerability factors. In Vale do Javari, other studies have shown that indigenous populations are also affected by a substantially higher prevalence of hepatitis B virus infection [24]. Alto Javari is an extensive area characterized by a combination of isolated indigenous communities, strong illegal exploitation of natural resources and, more recently, intense drug trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…This DSEI also presented high levels of the three vulnerability factors. In Vale do Javari, other studies have shown that indigenous populations are also affected by a substantially higher prevalence of hepatitis B virus infection [24]. Alto Javari is an extensive area characterized by a combination of isolated indigenous communities, strong illegal exploitation of natural resources and, more recently, intense drug trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…Las coinfecciones del VHB con los retrovirus como el virus de inmunodeficiencia humana (VIH) y el virus linfotrópico de células T humanas (HTLV, por sus siglas en inglés) tipo 1 y 2 hacen más compleja la prevención y el control de estas infecciones (7) , sobre todo en zonas rurales con poco acceso a los servicios de salud, como en las comunidades indígenas de la Amazonía (8) . En estas comunidades también se han descrito prevalencias de 5,9% y 3,8%…”
Section: Introductionunclassified
“…This value is almost 20 times higher than the annual mean API in the Amazon region, in the same period (mean API: 11 cases/1,000 inhabitants) 3 . In 1994, the National Health Foundation reported an important number of deaths in the indigenous population that was initially attributed to hepatitis, but was later demonstrated to be malaria, the main cause of morbidity and mortality in that outbreak 21 , 23 . Sampaio et al .…”
Section: Discussionmentioning
confidence: 99%